Information Infrastructure : The World Bank Group's Experience - Barbu, Alain; Dominguez, Rafael; Melody, William (Washington, DC: World Bank and the International Finance Corporation, 2013)
This joint OED(Operations Evaluation Department)/OEG (Operations Evaluation Group) study follows up OED's 1993 review of the Bank's experience in telecommunications. It assesses how World Bank Group assistance from 1993 onward has influenced the development of information infrastructure in developing countries. It finds that recommendations of the 1993 review have generally been heeded with a) the adoption of a new private-sector-led agenda; b) the incorporation of the new agenda in most recent Bank lending and non-lending interventions; and c) the increasing share of IFC in total Bank Group funding commitments for telecommunications. The study points out that, at a time when the information revolution presents developing countries with far-reaching opportunities and risks, the Bank Group's ability to play a global policy leadership role has been hampered by its benign neglect of the sector at both the strategic and country management levels, as well as a fragmented internal organization. As a result, the number of countries where it has had a real impact is limited. The study recommends that the Bank Group a) restate its strategy in the broader information infrastructure, with a particular focus on optimizing the use of its instruments and expert skills; and b) gaps in the existing monitoring and evaluation systems be filled, to provide the necessary framework to assess the future effectiveness of the revised strategy.